Glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material and preparation method thereof

By using glass-covered high-entropy amorphous alloy fibers as reinforcement in aluminum-based composites, the limitations of existing aluminum-based composites are solved, and the high strength, toughness and hardness of the material are achieved, which is suitable for high-performance applications.

CN119876796APending Publication Date: 2025-04-25苏州创泰合金材料有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411000989.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-25
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing aluminum-based composite materials have limitations in performance and are difficult to meet the high-performance requirements for materials in the fields of aerospace and other fields.

Method used

The glass-coated high-entropy amorphous alloy fiber is used as the reinforcement of aluminum-based composite material, and the materials are prepared by low-temperature ball milling and plasma discharge sintering processes.

Benefits of technology

Improves the comprehensive mechanical properties of aluminum-based composite materials, including high strength, toughness and hardness, and is suitable for high-performance applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004961555190000181
    Figure BDA0004961555190000181
  • Figure BDA0004961555190000182
    Figure BDA0004961555190000182
  • Figure BDA0004961555190000183
    Figure BDA0004961555190000183
Patent Text Reader

Abstract

The invention discloses a glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material, which is composed of 85-95 wt% of an aluminum alloy matrix and 5-15 wt% of glass-coated high-entropy amorphous alloy fiber, the aluminum alloy comprises the following components: 5.5-6.2 wt% of Zn, 2.7-3.5 wt% of Mg, 3.5-4.0 wt% of Si, 1.3-2.2 wt% of Cu, less than or equal to 0.5 wt% of Fe, and the balance of Al; the high-entropy amorphous alloy comprises the following components: 25 to 35 at% of Co, 15 to 25 at% of Fe, 5 to 10 at% of Ta, 5 to 10 at% of Nb, 25 to 30 at% of B and 5 to 10 at% of Si. The high-entropy amorphous alloy has the characteristics of the high-entropy alloy and the amorphous alloy, so that the fiber has high strength, high toughness and high stability, the hardness and corrosion resistance of the material can be effectively improved through glass coating, and the glass-coated high-entropy amorphous alloy fiber serves as a reinforcement to enable the aluminum-based composite material to obtain excellent comprehensive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of alloys, and in particular to a glass-coated high-entropy amorphous alloy fiber. Background Art

[0002] Aluminum alloy has the advantages of light weight, high strength, excellent wear resistance, good thermal conductivity, etc. It is an ideal material in the fields of aerospace, electric power, automobile, military industry, etc. It is widely used in high-strength, heat dissipation, wear-resistant and other working occasions. In addition, the content of aluminum element is abundant in the earth's crust, second only to oxygen and silicon, ranking first among metal elements. The abundant resource reserves also make the development prospects of aluminum-based materials broad. The rapid development of modern science and technology, especially the development of aviation and aerospace technology, has put forward increasingly higher requirements on material performance, which requires materials to have various special properties or excellent comprehensive properties. It is difficult to meet these performance requirements by simply optimizing the composition and heat treatment process of aluminum alloy. In order to overcome the limitations of aluminum alloy performance and obtain various special properties or excellent comprehensive properties, aluminum-based composite materials with various reinforcement phases have been deeply studied and rapidly developed. According to the different reinforcements, aluminum-based composite materials can be divided into fiber-reinforced aluminum-based composite materials, particle-reinforced aluminum-based composite materials, whisker-reinforced aluminum-based composite materials and new aluminum-based composite materials. Among them, fiber-reinforced aluminum-based composite materials have become the main type of aluminum-based composite materials due to their advantages of good high-temperature performance, high specific strength and specific modulus, good electrical and thermal conductivity, non-hygroscopicity, and non-aging. They show great application potential and are mainly used in the aerospace field and the automotive industry to manufacture various structural parts and components to reduce structural weight and improve performance. In terms of fiber size, fiber-reinforced aluminum-based composite materials can be divided into continuous fiber-reinforced and discontinuous fiber-reinforced aluminum-based composite materials, in which the length of the continuous fiber can run through the entire metal matrix, making the material show obvious anisotropy, while the length of the discontinuous fiber is generally several millimeters, making the material show isotropy. At present, the methods for preparing aluminum-based composite materials are mainly divided into three categories according to the state of the material during forming: liquid, semi-solid and solid forming. Among them, the liquid forming methods mainly include stirring casting, pressure infiltration, selective laser melting, etc.; the main methods of solid forming include stirring friction and powder metallurgy, etc.; other methods include semi-solid stirring, in-situ synthesis, etc. Powder metallurgy is the most widely used method for preparing aluminum-based composite materials by solid method. This method refers to a forming process that uses pure aluminum or aluminum alloy powder particles as raw materials and uses related processes to consolidate the powder into a specific shape. It can effectively avoid alloy component segregation and maintain the original grain size in the powder, thereby obtaining excellent mechanical properties. Summary of the invention

[0003] Technical problem to be solved: The technical problem to be solved by the present invention is to provide a glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material.

[0004] Technical solution: A glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material, consisting of 85-95wt% aluminum alloy matrix and 5-15wt% glass-coated high-entropy amorphous alloy fiber. Preferably, the method for preparing the glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material comprises the following steps: S1. The glass-coated high entropy amorphous alloy fiber and the aluminum alloy powder are weighed according to the weight ratio, placed in a low-temperature ball mill and filled with liquid nitrogen, and low-temperature ball milling is performed to mix the raw materials evenly; S2. The mixed raw materials are placed in a mold, and a pre-pressure is applied to compact the mixed raw materials to obtain a pre-pressed green body; S3. Place the green body into a plasma discharge sintering furnace, pressurize and evacuate, heat up for sintering and keep warm, take it out after the furnace cools to room temperature, and obtain a glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material. Preferably, the method for preparing the glass-coated high-entropy amorphous alloy fiber comprises the following steps: S11. Calculate and weigh the required weight of each component of the high entropy amorphous alloy according to the atomic percentage, put it into the crucible of the arc melting furnace and evacuate it, and repeatedly melt it until the composition is uniform to obtain a master alloy ingot; S12. The master alloy ingot is moved to a special crucible for suction casting, the master alloy ingot is heated and melted, and suction casting is performed to obtain a cylindrical master alloy ingot, which is then cut into short cylindrical billets; S13. The short cylindrical blank is loaded into a glass tube with a tapered bottom, fixed on a wire drawing device and the inside of the tube is evacuated, heated until the master alloy ingot is melted and the glass tube is softened, and then wire drawing is performed and rapidly water-cooled to obtain glass-coated high-entropy amorphous alloy fibers. Preferably, in step S1, the glass-coated high-entropy amorphous alloy fiber has a diameter of 10 to 30 μm, a length of 20 to 50 mm, and a thickness of the glass coating layer of 2 to 7 μm. Preferably, the particle size of the aluminum alloy powder in step S1 is 5 to 20 μm. Preferably, in step S3, the sintering pressure is 35-45 MPa, the sintering temperature is 500-550° C., and the holding time is 10-20 min. Preferably, the diameter of the short cylindrical blank in step S12 is 4 to 6 mm. Preferably, in step S13, the inner diameter of the glass tube is 4-6 mm, and the outer diameter is 6-8 mm. Preferably, the composition of the high entropy amorphous alloy consists of the following atomic percentages: Co: 25-35at%, Fe: 15-25at%, Ta: 5-10at%, Nb: 5-10at%, B: 25-30at%, Si: 5-10at%. Preferably, the aluminum alloy has a composition in the following weight ratio: Zn: 5.5-6.2wt%, Mg: 2.7-3.5wt%, Si: 3.5-4.0wt%, Cu: 1.3-2.2wt%, Fe: 0.2wt%, and the balance is Al. Beneficial effects: Compared with the prior art, the present invention has the following characteristics: The glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material of the present invention uses the glass-coated high-entropy amorphous alloy fiber as a reinforcement of the aluminum-based composite material. The high-entropy amorphous alloy has the characteristics of both high-entropy alloy and amorphous alloy, so the fiber has good mechanical properties and stability. Using glass as a coating layer of the fiber can improve the hardness of the material, so that the aluminum-based composite material has excellent comprehensive performance. Amorphous alloys can also be called metallic glasses, because they are prepared by rapidly freezing the atomic structure from the liquid to form a disordered structure similar to glass. They have the properties of both metals and glasses, with the rigidity and strength of solid materials, and the amorphous structure and high plasticity of liquid materials. High entropy alloys, also known as multi-component alloys, equimolar alloys, equiatomic ratio alloys, substitution alloys and multi-principal element alloys, are traditionally defined as solid solution alloys composed of five or more elements with an atomic percentage of each component between 5% and 35%, in an equimolar or nearly equimolar ratio. High entropy amorphous alloys are a new type of material discovered in recent years that has both amorphous structure and high mixed entropy characteristics. Compared with amorphous alloys and high entropy alloys, high entropy amorphous alloys have the structural characteristics of long-range disorder and short-range order of amorphous alloys and the four major effects of high entropy. Therefore, they have excellent mechanical, physical and chemical properties and are the preferred reinforcement in composite materials. According to the size and shape of amorphous alloy materials, they can be divided into five categories: block, strip, film, powder and wire. Among them, amorphous alloy wire is an amorphous alloy wire with a diameter of micrometer level. Due to its special structure of ultrafine nanocrystals, it has better strength, toughness, thermal conductivity and electrical conductivity than traditional metal wire. However, the special structure and properties of amorphous make it impossible to prepare amorphous wire materials with very fine diameters through cold drawing or hot drawing processes of ordinary alloys, which limits the application of amorphous wire. In order to prepare high-quality amorphous wire, glass coating is introduced into the melt drawing method, that is, the alloy is placed in a glass tube for heating and drawing and rapid water cooling to obtain amorphous alloy wire. The glass layer can protect the amorphous wire and prevent the amorphous wire from being oxidized during the melting and cooling process, so as to prepare amorphous wire with high roundness and uniform thickness. At the same time, glass has high hardness and good corrosion resistance. The glass-coated amorphous alloy wire is used as a fiber reinforcement of the composite material as a whole, which can effectively improve the comprehensive mechanical properties of the material. Compared with the prior art, the present invention has the following advantages and positive effects: The present invention uses glass-coated high-entropy amorphous alloy fibers as reinforcements. The high-entropy amorphous alloy fibers have high strength and high toughness, and the glass has high hardness. The combination of the two can effectively improve the comprehensive mechanical properties of the aluminum-based composite material. The present invention adopts a melt drawing method to prepare glass-coated high-entropy amorphous alloy fibers, which has a simple process, high stability, high fiber roundness and uniform thickness. The present invention adopts a plasma discharge sintering method to prepare the aluminum-based composite material, which has the advantages of simple operation, fast heating and sintering rates, controllable temperature and pressure, high material density and uniform microstructure. DETAILED DESCRIPTION In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. Specific preferred examples are as follows: Embodiment 1: A glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material, consisting of 95wt% aluminum alloy matrix and 5wt% glass-coated high-entropy amorphous alloy fiber; The preparation method of the glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material comprises the following steps: S1. The glass-coated high entropy amorphous alloy fiber and the aluminum alloy powder are weighed according to the weight ratio, placed in a low-temperature ball mill and filled with liquid nitrogen, and low-temperature ball milling is performed to mix the raw materials evenly; S2. The mixed raw materials are placed in a mold, and a pre-pressure is applied to compact the mixed raw materials to obtain a pre-pressed green body; S3. Place the green body into a plasma discharge sintering furnace, pressurize and evacuate, heat and sinter, and keep warm. The sintering pressure is 45MPa, the sintering temperature is 500°C, and the holding time is 20min. After the furnace is cooled to room temperature, take it out to obtain a glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material; The method for preparing the glass-coated high-entropy amorphous alloy fiber comprises the following steps: S11. Calculate and weigh the required weight of each component of the high entropy amorphous alloy according to the atomic percentage, put it into the crucible of the arc melting furnace and evacuate it, and repeatedly melt it until the composition is uniform to obtain a master alloy ingot; S12. The master alloy ingot is moved to a special crucible for suction casting, the master alloy ingot is heated and melted, and suction casting is performed to obtain a cylindrical master alloy ingot with a diameter of 5 mm, and cut into short cylindrical billets; S13. The short cylindrical billet is loaded into a glass tube with a tapered bottom, the inner diameter of the glass tube is 5 mm, the outer diameter is 7 mm, fixed on a wire drawing device and the tube is evacuated, heated until the master alloy ingot is melted and the glass tube is softened, and wire drawing is performed and rapidly water-cooled to obtain a glass-coated high entropy amorphous alloy fiber; In step S1, the diameter of the glass-coated high entropy amorphous alloy fiber is 10-15 μm, the length is 20-50 mm, and the thickness of the glass coating layer is 2-4 μm; The particle size of the aluminum alloy powder in step S1 is 5 to 20 μm; The composition of the high entropy amorphous alloy consists of the following atomic percentages: Co: 35at%, Fe: 15at%, Ta: 10at%, Nb: 5at%, B: 25at%, Si: 10at%; The aluminum alloy has a composition consisting of the following weight ratios: Zn: 5.5wt%, Mg: 3.5wt%, Si: 3.7wt%, Cu: 1.8wt%, Fe: 0.2wt%, and the balance is Al. Embodiment 2: A glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material, consisting of 90wt% of an aluminum alloy matrix and 10wt% of a glass-coated high-entropy amorphous alloy fiber; The preparation method of the glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material comprises the following steps: S1. The glass-coated high entropy amorphous alloy fiber and the aluminum alloy powder are weighed according to the weight ratio, placed in a low-temperature ball mill and filled with liquid nitrogen, and low-temperature ball milling is performed to mix the raw materials evenly; S2. The mixed raw materials are placed in a mold, and a pre-pressure is applied to compact the mixed raw materials to obtain a pre-pressed green body; S3. Place the green body into a plasma discharge sintering furnace, pressurize and evacuate, heat and sinter, and keep warm. The sintering pressure is 45MPa, the sintering temperature is 500°C, and the holding time is 20min. After the furnace is cooled to room temperature, take it out to obtain a glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material; The method for preparing the glass-coated high-entropy amorphous alloy fiber comprises the following steps: S11. Calculate and weigh the required weight of each component of the high entropy amorphous alloy according to the atomic percentage, put it into the crucible of the arc melting furnace and evacuate it, and repeatedly melt it until the composition is uniform to obtain a master alloy ingot; S12. The master alloy ingot is moved to a special crucible for suction casting, the master alloy ingot is heated and melted, and suction casting is performed to obtain a cylindrical master alloy ingot with a diameter of 5 mm, and cut into short cylindrical billets; S13. The short cylindrical billet is loaded into a glass tube with a tapered bottom, the inner diameter of the glass tube is 5 mm, the outer diameter is 7 mm, fixed on a wire drawing device and the tube is evacuated, heated until the master alloy ingot is melted and the glass tube is softened, and wire drawing is performed and rapidly water-cooled to obtain a glass-coated high entropy amorphous alloy fiber; In step S1, the diameter of the glass-coated high entropy amorphous alloy fiber is 10-15 μm, the length is 20-50 mm, and the thickness of the glass coating layer is 2-4 μm; The particle size of the aluminum alloy powder in step S1 is 5 to 20 μm; The composition of the high entropy amorphous alloy consists of the following atomic percentages: Co: 35at%, Fe: 15at%, Ta: 10at%, Nb: 5at%, B: 25at%, Si: 10at%; The composition of the aluminum alloy is composed of the following weight ratios: Zn: 6.2wt%, Mg: 2.7wt%, Si: 3.9wt%, Cu: 2.0wt%, Fe: 0.1wt%, and the balance is Al. Embodiment 3: A glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material, consisting of 85wt% aluminum alloy matrix and 15wt% glass-coated high-entropy amorphous alloy fiber; The preparation method of the glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material comprises the following steps: S1. The glass-coated high entropy amorphous alloy fiber and the aluminum alloy powder are weighed according to the weight ratio, placed in a low-temperature ball mill and filled with liquid nitrogen, and low-temperature ball milling is performed to mix the raw materials evenly; S2. The mixed raw materials are placed in a mold, and a pre-pressure is applied to compact the mixed raw materials to obtain a pre-pressed green body; S3. Place the green body into a plasma discharge sintering furnace, pressurize and evacuate, heat and sinter, and keep warm. The sintering pressure is 45MPa, the sintering temperature is 500°C, and the holding time is 20min. After the furnace is cooled to room temperature, take it out to obtain a glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material; The method for preparing the glass-coated high-entropy amorphous alloy fiber comprises the following steps: S11. Calculate and weigh the required weight of each component of the high entropy amorphous alloy according to the atomic percentage, put it into the crucible of the arc melting furnace and evacuate it, and repeatedly melt it until the composition is uniform to obtain a master alloy ingot; S12. The master alloy ingot is moved to a special crucible for suction casting, the master alloy ingot is heated and melted, and suction casting is performed to obtain a cylindrical master alloy ingot with a diameter of 5 mm, and cut into short cylindrical billets; S13. The short cylindrical billet is loaded into a glass tube with a tapered bottom, the inner diameter of the glass tube is 5 mm, the outer diameter is 7 mm, fixed on a wire drawing device and the tube is evacuated, heated until the master alloy ingot is melted and the glass tube is softened, and wire drawing is performed and rapidly water-cooled to obtain a glass-coated high entropy amorphous alloy fiber; In step S1, the diameter of the glass-coated high entropy amorphous alloy fiber is 10-15 μm, the length is 20-50 mm, and the thickness of the glass coating layer is 2-4 μm; The particle size of the aluminum alloy powder in step S1 is 5 to 20 μm; The composition of the high entropy amorphous alloy consists of the following atomic percentages: Co: 35at%, Fe: 15at%, Ta: 10at%, Nb: 5at%, B: 25at%, Si: 10at%; The aluminum alloy has a composition consisting of the following weight ratios: Zn: 5.8 wt %, Mg: 3.2 wt %, Si: 4.0 wt %, Cu: 1.3 wt %, Fe: 0.5 wt %, and the balance is Al. Embodiment 4: A glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material, consisting of 90wt% of an aluminum alloy matrix and 10wt% of a glass-coated high-entropy amorphous alloy fiber; The preparation method of the glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material comprises the following steps: S1. The glass-coated high entropy amorphous alloy fiber and the aluminum alloy powder are weighed according to the weight ratio, placed in a low-temperature ball mill and filled with liquid nitrogen, and low-temperature ball milling is performed to mix the raw materials evenly; S2. The mixed raw materials are placed in a mold, and a pre-pressure is applied to compact the mixed raw materials to obtain a pre-pressed green body; S3. The green body is placed in a plasma discharge sintering furnace, pressurized and evacuated, heated and sintered and kept warm, the sintering pressure is 40MPa, the sintering temperature is 525℃, the holding time is 15min, the furnace is cooled to room temperature and then taken out to obtain a glass-coated high entropy amorphous alloy fiber reinforced aluminum-based composite material; The method for preparing the glass-coated high-entropy amorphous alloy fiber comprises the following steps: S11. Calculate and weigh the required weight of each component of the high entropy amorphous alloy according to the atomic percentage, put it into the crucible of the arc melting furnace and evacuate it, and repeatedly melt it until the composition is uniform to obtain a master alloy ingot; S12. The master alloy ingot is moved to a special crucible for suction casting, the master alloy ingot is heated and melted, and suction casting is performed to obtain a cylindrical master alloy ingot with a diameter of 5 mm, and cut into short cylindrical billets; S13. The short cylindrical billet is loaded into a glass tube with a tapered bottom, the inner diameter of the glass tube is 5 mm, the outer diameter is 7 mm, fixed on a wire drawing device and the tube is evacuated, heated until the master alloy ingot is melted and the glass tube is softened, and wire drawing is performed and rapidly water-cooled to obtain a glass-coated high entropy amorphous alloy fiber; In step S1, the diameter of the glass-coated high entropy amorphous alloy fiber is 10-15 μm, the length is 20-50 mm, and the thickness of the glass coating layer is 2-4 μm; The particle size of the aluminum alloy powder in step S1 is 5 to 20 μm; The composition of the high entropy amorphous alloy consists of the following atomic percentages: Co: 35at%, Fe: 15at%, Ta: 10at%, Nb: 5at%, B: 25at%, Si: 10at%; The aluminum alloy has a composition consisting of the following weight ratios: Zn: 5.6 wt %, Mg: 2.9 wt %, Si: 3.5 wt %, Cu: 2.2 wt %, and the balance being Al. Embodiment 5: A glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material, consisting of 90wt% of an aluminum alloy matrix and 10wt% of a glass-coated high-entropy amorphous alloy fiber; The preparation method of the glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material comprises the following steps: S1. The glass-coated high entropy amorphous alloy fiber and the aluminum alloy powder are weighed according to the weight ratio, placed in a low-temperature ball mill and filled with liquid nitrogen, and low-temperature ball milling is performed to mix the raw materials evenly; S2. The mixed raw materials are placed in a mold, and a pre-pressure is applied to compact the mixed raw materials to obtain a pre-pressed green body; S3. The green body is placed in a plasma discharge sintering furnace, pressurized and evacuated, heated and sintered and kept warm, the sintering pressure is 35MPa, the sintering temperature is 550℃, the holding time is 10min, the furnace is cooled to room temperature and then taken out to obtain a glass-coated high entropy amorphous alloy fiber reinforced aluminum matrix composite material; The method for preparing the glass-coated high-entropy amorphous alloy fiber comprises the following steps: S11. Calculate and weigh the required weight of each component of the high entropy amorphous alloy according to the atomic percentage, put it into the crucible of the arc melting furnace and evacuate it, and repeatedly melt it until the composition is uniform to obtain a master alloy ingot; S12. The master alloy ingot is moved to a special crucible for suction casting, the master alloy ingot is heated and melted, and suction casting is performed to obtain a cylindrical master alloy ingot with a diameter of 5 mm, and cut into short cylindrical billets; S13. The short cylindrical billet is loaded into a glass tube with a tapered bottom, the inner diameter of the glass tube is 5 mm, the outer diameter is 7 mm, fixed on a wire drawing device and the tube is evacuated, heated until the master alloy ingot is melted and the glass tube is softened, and wire drawing is performed and rapidly water-cooled to obtain a glass-coated high entropy amorphous alloy fiber; In step S1, the diameter of the glass-coated high entropy amorphous alloy fiber is 10-15 μm, the length is 20-50 mm, and the thickness of the glass coating layer is 2-4 μm; The particle size of the aluminum alloy powder in step S1 is 5 to 20 μm; The composition of the high entropy amorphous alloy consists of the following atomic percentages: Co: 35at%, Fe: 15at%, Ta: 10at%, Nb: 5at%, B: 25at%, Si: 10at%; The aluminum alloy has a composition consisting of the following weight ratios: Zn: 6.0 wt %, Mg: 3.3 wt %, Si: 3.9 wt %, Cu: 1.5 wt %, Fe: 0.2 wt %, and the balance is Al. Embodiment 6: A glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material, consisting of 90wt% of an aluminum alloy matrix and 10wt% of a glass-coated high-entropy amorphous alloy fiber; The preparation method of the glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material comprises the following steps: S1. The glass-coated high entropy amorphous alloy fiber and the aluminum alloy powder are weighed according to the weight ratio, placed in a low-temperature ball mill and filled with liquid nitrogen, and low-temperature ball milling is performed to mix the raw materials evenly; S2. The mixed raw materials are placed in a mold, and a pre-pressure is applied to compact the mixed raw materials to obtain a pre-pressed green body; S3. The green body is placed in a plasma discharge sintering furnace, pressurized and evacuated, heated and sintered and kept warm, the sintering pressure is 40MPa, the sintering temperature is 525℃, the holding time is 15min, the furnace is cooled to room temperature and then taken out to obtain a glass-coated high entropy amorphous alloy fiber reinforced aluminum-based composite material; The method for preparing the glass-coated high-entropy amorphous alloy fiber comprises the following steps: S11. Calculate and weigh the required weight of each component of the high entropy amorphous alloy according to the atomic percentage, put it into the crucible of the arc melting furnace and evacuate it, and repeatedly melt it until the composition is uniform to obtain a master alloy ingot; S12. The master alloy ingot is moved to a special crucible for suction casting, the master alloy ingot is heated and melted, and suction casting is performed to obtain a cylindrical master alloy ingot with a diameter of 5 mm, and cut into short cylindrical billets; S13. The short cylindrical billet is loaded into a glass tube with a tapered bottom, the inner diameter of the glass tube is 5 mm, the outer diameter is 7 mm, fixed on a wire drawing device and the tube is evacuated, heated until the master alloy ingot is melted and the glass tube is softened, and wire drawing is performed and rapidly water-cooled to obtain a glass-coated high entropy amorphous alloy fiber; In step S1, the diameter of the glass-coated high-entropy amorphous alloy fiber is 15-20 μm, the length is 20-50 mm, and the thickness of the glass coating layer is 3-5 μm; The particle size of the aluminum alloy powder in step S1 is 5 to 20 μm; The composition of the high entropy amorphous alloy consists of the following atomic percentages: Co: 35at%, Fe: 15at%, Ta: 10at%, Nb: 5at%, B: 25at%, Si: 10at%; The aluminum alloy has a composition consisting of the following weight ratios: Zn: 5.5wt%, Mg: 3.2wt%, Si: 3.8wt%, Cu: 2.1wt%, Fe: 0.5wt%, and the balance is Al. Embodiment 7: A glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material, consisting of 90wt% of an aluminum alloy matrix and 10wt% of a glass-coated high-entropy amorphous alloy fiber; The preparation method of the glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material comprises the following steps: S1. The glass-coated high entropy amorphous alloy fiber and the aluminum alloy powder are weighed according to the weight ratio, placed in a low-temperature ball mill and filled with liquid nitrogen, and low-temperature ball milling is performed to mix the raw materials evenly; S2. The mixed raw materials are placed in a mold, and a pre-pressure is applied to compact the mixed raw materials to obtain a pre-pressed green body; S3. The green body is placed in a plasma discharge sintering furnace, pressurized and evacuated, heated and sintered and kept warm, the sintering pressure is 40MPa, the sintering temperature is 525℃, the holding time is 15min, the furnace is cooled to room temperature and then taken out to obtain a glass-coated high entropy amorphous alloy fiber reinforced aluminum-based composite material; The method for preparing the glass-coated high-entropy amorphous alloy fiber comprises the following steps: S11. Calculate and weigh the required weight of each component of the high entropy amorphous alloy according to the atomic percentage, put it into the crucible of the arc melting furnace and evacuate it, and repeatedly melt it until the composition is uniform to obtain a master alloy ingot; S12. The master alloy ingot is moved to a special crucible for suction casting, the master alloy ingot is heated and melted, and suction casting is performed to obtain a cylindrical master alloy ingot with a diameter of 5 mm, and cut into short cylindrical billets; S13. The short cylindrical billet is loaded into a glass tube with a tapered bottom, the inner diameter of the glass tube is 5 mm, the outer diameter is 7 mm, fixed on a wire drawing device and the tube is evacuated, heated until the master alloy ingot is melted and the glass tube is softened, and wire drawing is performed and rapidly water-cooled to obtain a glass-coated high entropy amorphous alloy fiber; In step S1, the diameter of the glass-coated high entropy amorphous alloy fiber is 20-25 μm, the length is 20-50 mm, and the thickness of the glass coating layer is 4-6 μm; The particle size of the aluminum alloy powder in step S1 is 5 to 20 μm; The composition of the high entropy amorphous alloy consists of the following atomic percentages: Co: 35at%, Fe: 15at%, Ta: 10at%, Nb: 5at%, B: 25at%, Si: 10at%; The aluminum alloy has a composition consisting of the following weight ratios: Zn: 5.6 wt %, Mg: 2.7 wt %, Si: 3.9 wt %, Cu: 1.7 wt %, Fe: 0.3 wt %, and the balance is Al. Embodiment 8: A glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material, consisting of 90wt% of an aluminum alloy matrix and 10wt% of a glass-coated high-entropy amorphous alloy fiber; The preparation method of the glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material comprises the following steps: S1. The glass-coated high entropy amorphous alloy fiber and the aluminum alloy powder are weighed according to the weight ratio, placed in a low-temperature ball mill and filled with liquid nitrogen, and low-temperature ball milling is performed to mix the raw materials evenly; S2. The mixed raw materials are placed in a mold, and a pre-pressure is applied to compact the mixed raw materials to obtain a pre-pressed green body; S3. The green body is placed in a plasma discharge sintering furnace, pressurized and evacuated, heated and sintered and kept warm, the sintering pressure is 40MPa, the sintering temperature is 525℃, the holding time is 15min, the furnace is cooled to room temperature and then taken out to obtain a glass-coated high entropy amorphous alloy fiber reinforced aluminum-based composite material; The method for preparing the glass-coated high-entropy amorphous alloy fiber comprises the following steps: S11. Calculate and weigh the required weight of each component of the high entropy amorphous alloy according to the atomic percentage, put it into the crucible of the arc melting furnace and evacuate it, and repeatedly melt it until the composition is uniform to obtain a master alloy ingot; S12. The master alloy ingot is moved to a special crucible for suction casting, the master alloy ingot is heated and melted, and suction casting is performed to obtain a cylindrical master alloy ingot with a diameter of 5 mm, and cut into short cylindrical billets; S13. The short cylindrical billet is loaded into a glass tube with a tapered bottom, the inner diameter of the glass tube is 5 mm, the outer diameter is 7 mm, fixed on a wire drawing device and the tube is evacuated, heated until the master alloy ingot is melted and the glass tube is softened, and wire drawing is performed and rapidly water-cooled to obtain a glass-coated high entropy amorphous alloy fiber; In step S1, the diameter of the glass-coated high entropy amorphous alloy fiber is 25-30 μm, the length is 20-50 mm, and the thickness of the glass coating layer is 5-7 μm; The particle size of the aluminum alloy powder in step S1 is 5 to 20 μm; The composition of the high entropy amorphous alloy consists of the following atomic percentages: Co: 35at%, Fe: 15at%, Ta: 10at%, Nb: 5at%, B: 25at%, Si: 10at%; The aluminum alloy has a composition consisting of the following weight ratios: Zn: 6.1 wt %, Mg: 2.9 wt %, Si: 3.7 wt %, Cu: 2.2 wt %, Fe: 0.4 wt %, and the balance is Al. Embodiment 9: A glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material, consisting of 90wt% of an aluminum alloy matrix and 10wt% of a glass-coated high-entropy amorphous alloy fiber; The preparation method of the glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material comprises the following steps: S1. The glass-coated high entropy amorphous alloy fiber and the aluminum alloy powder are weighed according to the weight ratio, placed in a low-temperature ball mill and filled with liquid nitrogen, and low-temperature ball milling is performed to mix the raw materials evenly; S2. The mixed raw materials are placed in a mold, and a pre-pressure is applied to compact the mixed raw materials to obtain a pre-pressed green body; S3. The green body is placed in a plasma discharge sintering furnace, pressurized and evacuated, heated and sintered and kept warm, the sintering pressure is 40MPa, the sintering temperature is 525℃, the holding time is 15min, the furnace is cooled to room temperature and then taken out to obtain a glass-coated high entropy amorphous alloy fiber reinforced aluminum-based composite material; The method for preparing the glass-coated high-entropy amorphous alloy fiber comprises the following steps: S11. Calculate and weigh the required weight of each component of the high entropy amorphous alloy according to the atomic percentage, put it into the crucible of the arc melting furnace and evacuate it, and repeatedly melt it until the composition is uniform to obtain a master alloy ingot; S12. The master alloy ingot is moved to a special crucible for suction casting, the master alloy ingot is heated and melted, and suction casting is performed to obtain a cylindrical master alloy ingot with a diameter of 5 mm, and cut into short cylindrical billets; S13. The short cylindrical billet is loaded into a glass tube with a tapered bottom, the inner diameter of the glass tube is 5 mm, the outer diameter is 7 mm, fixed on a wire drawing device and the tube is evacuated, heated until the master alloy ingot is melted and the glass tube is softened, and wire drawing is performed and rapidly water-cooled to obtain a glass-coated high entropy amorphous alloy fiber; In step S1, the diameter of the glass-coated high-entropy amorphous alloy fiber is 15-20 μm, the length is 20-50 mm, and the thickness of the glass coating layer is 3-5 μm; The particle size of the aluminum alloy powder in step S1 is 5 to 20 μm; The composition of the high entropy amorphous alloy consists of the following atomic percentages: Co: 30at%, Fe: 20at%, Ta: 10at%, Nb: 5at%, B: 25at%, Si: 10at%; The aluminum alloy has a composition consisting of the following weight ratios: Zn: 5.7 wt %, Mg: 3.0 wt %, Si: 4.0 wt %, Cu: 1.4 wt %, Fe: 0.2 wt %, and the balance is Al. Embodiment 10: A glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material, consisting of 90wt% of an aluminum alloy matrix and 10wt% of a glass-coated high-entropy amorphous alloy fiber; The preparation method of the glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material comprises the following steps: S1. The glass-coated high entropy amorphous alloy fiber and the aluminum alloy powder are weighed according to the weight ratio, placed in a low-temperature ball mill and filled with liquid nitrogen, and low-temperature ball milling is performed to mix the raw materials evenly; S2. The mixed raw materials are placed in a mold, and a pre-pressure is applied to compact the mixed raw materials to obtain a pre-pressed green body; S3. The green body is placed in a plasma discharge sintering furnace, pressurized and evacuated, heated and sintered and kept warm, the sintering pressure is 40MPa, the sintering temperature is 525℃, the holding time is 15min, the furnace is cooled to room temperature and then taken out to obtain a glass-coated high entropy amorphous alloy fiber reinforced aluminum-based composite material; The method for preparing the glass-coated high-entropy amorphous alloy fiber comprises the following steps: S11. Calculate and weigh the required weight of each component of the high entropy amorphous alloy according to the atomic percentage, put it into the crucible of the arc melting furnace and evacuate it, and repeatedly melt it until the composition is uniform to obtain a master alloy ingot; S12. The master alloy ingot is moved to a special crucible for suction casting, the master alloy ingot is heated and melted, and suction casting is performed to obtain a cylindrical master alloy ingot with a diameter of 5 mm, and cut into short cylindrical billets; S13. The short cylindrical billet is loaded into a glass tube with a tapered bottom, the inner diameter of the glass tube is 5 mm, the outer diameter is 7 mm, fixed on a wire drawing device and the tube is evacuated, heated until the master alloy ingot is melted and the glass tube is softened, and wire drawing is performed and rapidly water-cooled to obtain a glass-coated high entropy amorphous alloy fiber; In step S1, the diameter of the glass-coated high-entropy amorphous alloy fiber is 15-20 μm, the length is 20-50 mm, and the thickness of the glass coating layer is 3-5 μm; The particle size of the aluminum alloy powder in step S1 is 5 to 20 μm; The composition of the high entropy amorphous alloy consists of the following atomic percentages: Co: 25at%, Fe: 25at%, Ta: 10at%, Nb: 5at%, B: 25at%, Si: 10at%; The aluminum alloy has a composition consisting of the following weight ratios: Zn: 5.6 wt %, Mg: 2.9 wt %, Si: 3.7 wt %, Cu: 2.0 wt %, Fe: 0.1 wt %, and the balance is Al. Embodiment 11: A glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material, consisting of 90wt% of an aluminum alloy matrix and 10wt% of a glass-coated high-entropy amorphous alloy fiber; The preparation method of the glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material comprises the following steps: S1. The glass-coated high entropy amorphous alloy fiber and the aluminum alloy powder are weighed according to the weight ratio, placed in a low-temperature ball mill and filled with liquid nitrogen, and low-temperature ball milling is performed to mix the raw materials evenly; S2. The mixed raw materials are placed in a mold, and a pre-pressure is applied to compact the mixed raw materials to obtain a pre-pressed green body; S3. The green body is placed in a plasma discharge sintering furnace, pressurized and evacuated, heated and sintered and kept warm, the sintering pressure is 40MPa, the sintering temperature is 525℃, the holding time is 15min, the furnace is cooled to room temperature and then taken out to obtain a glass-coated high entropy amorphous alloy fiber reinforced aluminum-based composite material; The method for preparing the glass-coated high-entropy amorphous alloy fiber comprises the following steps: S11. Calculate and weigh the required weight of each component of the high entropy amorphous alloy according to the atomic percentage, put it into the crucible of the arc melting furnace and evacuate it, and repeatedly melt it until the composition is uniform to obtain a master alloy ingot; S12. The master alloy ingot is moved to a special crucible for suction casting, the master alloy ingot is heated and melted, and suction casting is performed to obtain a cylindrical master alloy ingot with a diameter of 5 mm, and cut into short cylindrical billets; S13. The short cylindrical billet is loaded into a glass tube with a tapered bottom, the inner diameter of the glass tube is 5 mm, the outer diameter is 7 mm, fixed on a wire drawing device and the tube is evacuated, heated until the master alloy ingot is melted and the glass tube is softened, and wire drawing is performed and rapidly water-cooled to obtain a glass-coated high entropy amorphous alloy fiber; In step S1, the diameter of the glass-coated high-entropy amorphous alloy fiber is 15-20 μm, the length is 20-50 mm, and the thickness of the glass coating layer is 3-5 μm; The particle size of the aluminum alloy powder in step S1 is 5 to 20 μm; The composition of the high entropy amorphous alloy consists of the following atomic percentages: Co: 30at%, Fe: 20at%, Ta: 5at%, Nb: 10at%, B: 25at%, Si: 10at%; The aluminum alloy has a composition consisting of the following weight ratios: Zn: 5.7 wt %, Mg: 3.2 wt %, Si: 3.8 wt %, Cu: 2.1 wt %, and the balance is Al. Embodiment 12: A glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material, consisting of 90wt% of an aluminum alloy matrix and 10wt% of a glass-coated high-entropy amorphous alloy fiber; The preparation method of the glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material comprises the following steps: S1. The glass-coated high entropy amorphous alloy fiber and the aluminum alloy powder are weighed according to the weight ratio, placed in a low-temperature ball mill and filled with liquid nitrogen, and low-temperature ball milling is performed to mix the raw materials evenly; S2. The mixed raw materials are placed in a mold, and a pre-pressure is applied to compact the mixed raw materials to obtain a pre-pressed green body; S3. The green body is placed in a plasma discharge sintering furnace, pressurized and evacuated, heated and sintered and kept warm, the sintering pressure is 40MPa, the sintering temperature is 525℃, the holding time is 15min, the furnace is cooled to room temperature and then taken out to obtain a glass-coated high entropy amorphous alloy fiber reinforced aluminum-based composite material; The method for preparing the glass-coated high-entropy amorphous alloy fiber comprises the following steps: S11. Calculate and weigh the required weight of each component of the high entropy amorphous alloy according to the atomic percentage, put it into the crucible of the arc melting furnace and evacuate it, and repeatedly melt it until the composition is uniform to obtain a master alloy ingot; S12. The master alloy ingot is moved to a special crucible for suction casting, the master alloy ingot is heated and melted, and suction casting is performed to obtain a cylindrical master alloy ingot with a diameter of 5 mm, and cut into short cylindrical billets; S13. The short cylindrical billet is loaded into a glass tube with a tapered bottom, the inner diameter of the glass tube is 5 mm, the outer diameter is 7 mm, fixed on a wire drawing device and the tube is evacuated, heated until the master alloy ingot is melted and the glass tube is softened, and wire drawing is performed and rapidly water-cooled to obtain a glass-coated high entropy amorphous alloy fiber; In step S1, the diameter of the glass-coated high-entropy amorphous alloy fiber is 15-20 μm, the length is 20-50 mm, and the thickness of the glass coating layer is 3-5 μm; The particle size of the aluminum alloy powder in step S1 is 5 to 20 μm; The composition of the high entropy amorphous alloy consists of the following atomic percentages: Co: 30at%, Fe: 20at%, Ta: 10at%, Nb: 5at%, B: 30at%, Si: 5at%; The composition of the aluminum alloy consists of the following weight ratios: Zn: 6.1wt%, Mg: 2.7wt%, Si: 3.6wt%, Cu: 1.6wt%, Fe: 0.4wt%, and the balance is Al. In order to further illustrate the technical effect of the present invention, the present invention also provides a comparative example, which is as follows: Comparative Example 1: An aluminum-based composite material, consisting of 80wt% of an aluminum alloy matrix and 20wt% of a glass-coated high-entropy amorphous alloy fiber; a method for preparing the glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material comprises the following steps: S1. The glass-coated high entropy amorphous alloy fiber and the aluminum alloy powder are weighed according to the weight ratio, placed in a low-temperature ball mill and filled with liquid nitrogen, and low-temperature ball milling is performed to mix the raw materials evenly; S2. The mixed raw materials are placed in a mold, and a pre-pressure is applied to compact the mixed raw materials to obtain a pre-pressed green body; S3. Place the green body into a plasma discharge sintering furnace, pressurize and evacuate, heat and sinter, and keep warm. The sintering pressure is 45MPa, the sintering temperature is 500°C, and the holding time is 20min. After the furnace is cooled to room temperature, take it out to obtain a glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material; The method for preparing the glass-coated high-entropy amorphous alloy fiber comprises the following steps: S11. Calculate and weigh the required weight of each component of the high entropy amorphous alloy according to the atomic percentage, put it into the crucible of the arc melting furnace and evacuate it, and repeatedly melt it until the composition is uniform to obtain a master alloy ingot; S12. The master alloy ingot is moved to a special crucible for suction casting, the master alloy ingot is heated and melted, and suction casting is performed to obtain a cylindrical master alloy ingot with a diameter of 5 mm, and cut into short cylindrical billets; S13. The short cylindrical billet is loaded into a glass tube with a tapered bottom, the inner diameter of the glass tube is 5 mm, the outer diameter is 7 mm, fixed on a wire drawing device and the tube is evacuated, heated until the master alloy ingot is melted and the glass tube is softened, and wire drawing is performed and rapidly water-cooled to obtain a glass-coated high entropy amorphous alloy fiber; In step S1, the diameter of the glass-coated high entropy amorphous alloy fiber is 10-15 μm, the length is 20-50 mm, and the thickness of the glass coating layer is 2-4 μm; The particle size of the aluminum alloy powder in step S1 is 5 to 20 μm; The composition of the high entropy amorphous alloy consists of the following atomic percentages: Co: 35at%, Fe: 15at%, Ta: 10at%, Nb: 5at%, B: 25at%, Si: 10at%; The aluminum alloy has a composition consisting of the following weight ratios: Zn: 6.0 wt %, Mg: 2.9 wt %, Si: 3.5 wt %, Cu: 1.5 wt %, Fe: 0.2 wt %, and the balance is Al. Comparative Example 2: An aluminum-based composite material is composed of 90wt% of an aluminum alloy matrix and 10wt% of a glass-coated high-entropy amorphous alloy fiber; a method for preparing the glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material comprises the following steps: S1. The glass-coated high entropy amorphous alloy fiber and the aluminum alloy powder are weighed according to the weight ratio, placed in a low-temperature ball mill and filled with liquid nitrogen, and low-temperature ball milling is performed to mix the raw materials evenly; S2. The mixed raw materials are placed in a mold, and a pre-pressure is applied to compact the mixed raw materials to obtain a pre-pressed green body; S3. The green body is placed in a plasma discharge sintering furnace, pressurized and evacuated, heated and sintered and kept warm, the sintering pressure is 45MPa, the sintering temperature is 450°C, the holding time is 20min, the furnace is cooled to room temperature and then taken out to obtain a glass-coated high entropy amorphous alloy fiber reinforced aluminum-based composite material; The method for preparing the glass-coated high-entropy amorphous alloy fiber comprises the following steps: S11. Calculate and weigh the required weight of each component of the high entropy amorphous alloy according to the atomic percentage, put it into the crucible of the arc melting furnace and evacuate it, and repeatedly melt it until the composition is uniform to obtain a master alloy ingot; S12. The master alloy ingot is moved to a special crucible for suction casting, the master alloy ingot is heated and melted, and suction casting is performed to obtain a cylindrical master alloy ingot with a diameter of 5 mm, and cut into short cylindrical billets; S13. The short cylindrical billet is loaded into a glass tube with a tapered bottom, the inner diameter of the glass tube is 5 mm, the outer diameter is 7 mm, fixed on a wire drawing device and the tube is evacuated, heated until the master alloy ingot is melted and the glass tube is softened, and wire drawing is performed and rapidly water-cooled to obtain a glass-coated high entropy amorphous alloy fiber; In step S1, the diameter of the glass-coated high entropy amorphous alloy fiber is 10-15 μm, the length is 20-50 mm, and the thickness of the glass coating layer is 2-4 μm; The particle size of the aluminum alloy powder in step S1 is 5 to 20 μm; The composition of the high entropy amorphous alloy consists of the following atomic percentages: Co: 35at%, Fe: 15at%, Ta: 10at%, Nb: 5at%, B: 25at%, Si: 10at%; The aluminum alloy has a composition consisting of the following weight ratios: Zn: 5.9 wt %, Mg: 3.1 wt %, Si: 3.9 wt %, Cu: 1.9 wt %, Fe: 0.5 wt %, and the balance is Al. Comparative Example 3: An aluminum-based composite material is composed of 90wt% of an aluminum alloy matrix and 10wt% of a glass-coated high-entropy amorphous alloy fiber; a method for preparing the glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material comprises the following steps: S1. The glass-coated high entropy amorphous alloy fiber and the aluminum alloy powder are weighed according to the weight ratio, placed in a low-temperature ball mill and filled with liquid nitrogen, and low-temperature ball milling is performed to mix the raw materials evenly; S2. The mixed raw materials are placed in a mold, and a pre-pressure is applied to compact the mixed raw materials to obtain a pre-pressed green body; S3. The green body is placed in a plasma discharge sintering furnace, pressurized and evacuated, heated and sintered and kept warm, the sintering pressure is 35MPa, the sintering temperature is 600℃, the holding time is 10min, the furnace is cooled to room temperature and then taken out to obtain a glass-coated high entropy amorphous alloy fiber reinforced aluminum-based composite material; The method for preparing the glass-coated high-entropy amorphous alloy fiber comprises the following steps: S11. Calculate and weigh the required weight of each component of the high entropy amorphous alloy according to the atomic percentage, put it into the crucible of the arc melting furnace and evacuate it, and repeatedly melt it until the composition is uniform to obtain a master alloy ingot; S12. The master alloy ingot is moved to a special crucible for suction casting, the master alloy ingot is heated and melted, and suction casting is performed to obtain a cylindrical master alloy ingot with a diameter of 5 mm, and cut into short cylindrical billets; S13. The short cylindrical billet is loaded into a glass tube with a tapered bottom, the inner diameter of the glass tube is 5 mm, the outer diameter is 7 mm, fixed on a wire drawing device and the tube is evacuated, heated until the master alloy ingot is melted and the glass tube is softened, and wire drawing is performed and rapidly water-cooled to obtain a glass-coated high entropy amorphous alloy fiber; In step S1, the diameter of the glass-coated high entropy amorphous alloy fiber is 10-15 μm, the length is 20-50 mm, and the thickness of the glass coating layer is 2-4 μm; The particle size of the aluminum alloy powder in step S1 is 5 to 20 μm; The composition of the high entropy amorphous alloy consists of the following atomic percentages: Co: 35at%, Fe: 15at%, Ta: 10at%, Nb: 5at%, B: 25at%, Si: 10at%; The aluminum alloy has a composition consisting of the following weight ratios: Zn: 5.6 wt %, Mg: 3.1 wt %, Si: 3.6 wt %, Cu: 1.7 wt %, Fe: 0.3 wt %, and the balance is Al. Comparative Example 4: An aluminum-based composite material is composed of 90wt% of an aluminum alloy matrix and 10wt% of a glass-coated high-entropy amorphous alloy fiber; a method for preparing the glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material comprises the following steps: S1. The glass-coated high entropy amorphous alloy fiber and the aluminum alloy powder are weighed according to the weight ratio, placed in a low-temperature ball mill and filled with liquid nitrogen, and low-temperature ball milling is performed to mix the raw materials evenly; S2. The mixed raw materials are placed in a mold, and a pre-pressure is applied to compact the mixed raw materials to obtain a pre-pressed green body; S3. The green body is placed in a plasma discharge sintering furnace, pressurized and evacuated, heated and sintered and kept warm, the sintering pressure is 40MPa, the sintering temperature is 525℃, the holding time is 15min, the furnace is cooled to room temperature and then taken out to obtain a glass-coated high entropy amorphous alloy fiber reinforced aluminum-based composite material; The method for preparing the glass-coated high-entropy amorphous alloy fiber comprises the following steps: S11. Calculate and weigh the required weight of each component of the high entropy amorphous alloy according to the atomic percentage, put it into the crucible of the arc melting furnace and evacuate it, and repeatedly melt it until the composition is uniform to obtain a master alloy ingot; S12. The master alloy ingot is moved to a special crucible for suction casting, the master alloy ingot is heated and melted, and suction casting is performed to obtain a cylindrical master alloy ingot with a diameter of 5 mm, and cut into short cylindrical billets; S13. The short cylindrical billet is loaded into a glass tube with a tapered bottom, the inner diameter of the glass tube is 5 mm, the outer diameter is 7 mm, fixed on a wire drawing device and the tube is evacuated, heated until the master alloy ingot is melted and the glass tube is softened, and wire drawing is performed and rapidly water-cooled to obtain a glass-coated high entropy amorphous alloy fiber; In step S1, the diameter of the glass-coated high entropy amorphous alloy fiber is 30-35 μm, the length is 20-50 mm, and the thickness of the glass coating layer is 6-8 μm; The particle size of the aluminum alloy powder in step S1 is 5 to 20 μm; The composition of the high entropy amorphous alloy consists of the following atomic percentages: Co: 35at%, Fe: 15at%, Ta: 10at%, Nb: 5at%, B: 25at%, Si: 10at%; The aluminum alloy has a composition consisting of the following weight ratios: Zn: 5.8 wt %, Mg: 2.7 wt %, Si: 3.7 wt %, Cu: 2.1 wt %, Fe: 0.4 wt %, and the balance is Al. Comparative Example 5: An aluminum-based composite material is composed of 90wt% of an aluminum alloy matrix and 10wt% of a glass-coated high-entropy amorphous alloy fiber; a method for preparing the glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material comprises the following steps: S1. The glass-coated high entropy amorphous alloy fiber and the aluminum alloy powder are weighed according to the weight ratio, placed in a low-temperature ball mill and filled with liquid nitrogen, and low-temperature ball milling is performed to mix the raw materials evenly; S2. The mixed raw materials are placed in a mold, and a pre-pressure is applied to compact the mixed raw materials to obtain a pre-pressed green body; S3. The green body is placed in a plasma discharge sintering furnace, pressurized and evacuated, heated and sintered and kept warm, the sintering pressure is 40MPa, the sintering temperature is 525℃, the holding time is 15min, the furnace is cooled to room temperature and then taken out to obtain a glass-coated high entropy amorphous alloy fiber reinforced aluminum-based composite material; The method for preparing the glass-coated high-entropy amorphous alloy fiber comprises the following steps: S11. Calculate and weigh the required weight of each component of the high entropy amorphous alloy according to the atomic percentage, put it into the crucible of the arc melting furnace and evacuate it, and repeatedly melt it until the composition is uniform to obtain a master alloy ingot; S12. The master alloy ingot is moved to a special crucible for suction casting, the master alloy ingot is heated and melted, and suction casting is performed to obtain a cylindrical master alloy ingot with a diameter of 5 mm, and cut into short cylindrical billets; S13. The short cylindrical billet is loaded into a glass tube with a tapered bottom, the inner diameter of the glass tube is 5 mm, the outer diameter is 7 mm, fixed on a wire drawing device and the tube is evacuated, heated until the master alloy ingot is melted and the glass tube is softened, and wire drawing is performed and rapidly water-cooled to obtain a glass-coated high entropy amorphous alloy fiber; In step S1, the diameter of the glass-coated high entropy amorphous alloy fiber is 35-40 μm, the length is 20-50 mm, and the thickness of the glass coating layer is 7-9 μm; The particle size of the aluminum alloy powder in step S1 is 5 to 20 μm; The composition of the high entropy amorphous alloy consists of the following atomic percentages: Co: 35at%, Fe: 15at%, Ta: 10at%, Nb: 5at%, B: 25at%, Si: 10at%; The aluminum alloy has a composition consisting of the following weight ratios: Zn: 6.0 wt %, Mg: 2.8 wt %, Si: 3.7 wt %, Cu: 1.9 wt %, Fe: 0.1 wt %, and the balance is Al. Comparative Example 6: An aluminum-based composite material is composed of 90wt% of an aluminum alloy matrix and 10wt% of a glass-coated high-entropy amorphous alloy fiber; a method for preparing the glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material comprises the following steps: S1. The glass-coated high entropy amorphous alloy fiber and the aluminum alloy powder are weighed according to the weight ratio, placed in a low-temperature ball mill and filled with liquid nitrogen, and low-temperature ball milling is performed to mix the raw materials evenly; S2. The mixed raw materials are placed in a mold, and a pre-pressure is applied to compact the mixed raw materials to obtain a pre-pressed green body; S3. The green body is placed in a plasma discharge sintering furnace, pressurized and evacuated, heated and sintered and kept warm, the sintering pressure is 40MPa, the sintering temperature is 525℃, the holding time is 15min, the furnace is cooled to room temperature and then taken out to obtain a glass-coated high entropy amorphous alloy fiber reinforced aluminum-based composite material; The method for preparing the glass-coated high-entropy amorphous alloy fiber comprises the following steps: S11. Calculate and weigh the required weight of each component of the high entropy amorphous alloy according to the atomic percentage, put it into the crucible of the arc melting furnace and evacuate it, and repeatedly melt it until the composition is uniform to obtain a master alloy ingot; S12. The master alloy ingot is moved to a special crucible for suction casting, the master alloy ingot is heated and melted, and suction casting is performed to obtain a cylindrical master alloy ingot with a diameter of 5 mm, and cut into short cylindrical billets; S13. The short cylindrical billet is loaded into a glass tube with a tapered bottom, the inner diameter of the glass tube is 5 mm, the outer diameter is 7 mm, fixed on a wire drawing device and the tube is evacuated, heated until the master alloy ingot is melted and the glass tube is softened, and wire drawing is performed and rapidly water-cooled to obtain a glass-coated high entropy amorphous alloy fiber; In step S1, the diameter of the glass-coated high-entropy amorphous alloy fiber is 15-20 μm, the length is 20-50 mm, and the thickness of the glass coating layer is 3-5 μm; The particle size of the aluminum alloy powder in step S1 is 5 to 20 μm; The composition of the high entropy amorphous alloy consists of the following atomic percentages: Co: 75at%, Fe: 5at%, Ta: 5at%, Nb: 5at%, B: 5at%, Si: 5at%; The aluminum alloy has a composition consisting of the following weight ratios: Zn: 5.8 wt %, Mg: 2.9 wt %, Si: 3.6 wt %, Cu: 1.6 wt %, Fe: 0.1 wt %, and the balance is Al. Each embodiment and comparative example was prepared into a standard specimen, subjected to a tensile test, and tested for hardness using a microhardness tester, and the results are shown in Tables 1 to 4. In summary, each embodiment of the present invention has high hardness and high tensile strength, and has a high elongation at break, and has excellent comprehensive mechanical properties compared to the comparative example. Table 1 Effect of different fiber doping amounts on the mechanical properties of materials Table 2 Effect of different sintering temperatures on the mechanical properties of materials Table 3 Effect of different fiber diameters on the mechanical properties of materials Table 4 Effect of different components of high entropy amorphous alloys on the mechanical properties of materials

Claims

1. A glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material, characterized in that: The aluminum-based composite material consists of 85-95wt% of an aluminum alloy matrix and 5-15wt% of glass-coated high-entropy amorphous alloy fibers.

2. The method for preparing the glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material according to claim 1, characterized in that: The following steps are involved: S1. Weigh the glass-coated high entropy amorphous alloy fiber and the aluminum alloy powder according to the weight ratio, put them into a low-temperature ball mill and fill them with liquid nitrogen, and perform low-temperature ball milling to mix the raw materials evenly; S2. The mixed raw materials are placed in a mold, and a pre-pressure is applied to compact the mixed raw materials to obtain a pre-pressed green body; S3. Place the green body into a plasma discharge sintering furnace, pressurize and evacuate, heat up for sintering and keep warm, take it out after the furnace cools to room temperature, and obtain a glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material.

3. The glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material according to claim 1, characterized in that: The method for preparing the glass-coated high-entropy amorphous alloy fiber comprises the following steps: S11. Calculate and weigh the required weight of each component of the high entropy amorphous alloy according to the atomic percentage, put it into the crucible of the arc melting furnace and evacuate it, and repeatedly melt it until the composition is uniform to obtain a master alloy ingot; S12. The master alloy ingot is moved to a special crucible for suction casting, the master alloy ingot is heated and melted, and suction casting is performed to obtain a cylindrical master alloy ingot, which is then cut into short cylindrical billets; S13. The short cylindrical blank is loaded into a glass tube with a tapered bottom, fixed on a wire drawing device and the inside of the tube is evacuated, heated until the master alloy ingot is melted and the glass tube is softened, and then wire drawing is performed and rapidly water-cooled to obtain glass-coated high-entropy amorphous alloy fibers.

4. The method for preparing the glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material according to claim 2, characterized in that: In the step S1, the diameter of the glass-coated high-entropy amorphous alloy fiber is 10-30 μm, the length is 20-50 mm, and the thickness of the glass coating layer is 2-7 μm.

5. The method for preparing the glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material according to claim 2, characterized in that: The particle size of the aluminum alloy powder in step S1 is 5 to 20 μm.

6. The method for preparing the glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material according to claim 2, characterized in that: In step S3, the sintering pressure is 35-45 MPa, the sintering temperature is 500-550° C., and the holding time is 10-20 min.

7. The glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material according to claim 3, characterized in that: In step S12, the diameter of the short cylindrical blank is 4 to 6 mm.

8. The glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material according to claim 3, characterized in that: In step S13, the inner diameter of the glass tube is 4-6 mm, and the outer diameter is 6-8 mm.

9. The glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material according to claim 1, characterized in that: The high entropy amorphous alloy comprises the following atomic percentages: Co: 25-35 at%, Fe: 15-25 at%, Ta: 5-10 at%, Nb: 5-10 at%, B: 25-30 at%, Si: 5-10 at%.

10. The glass-coated high-entropy amorphous alloy fiber reinforced aluminum-based composite material according to claim 1, characterized in that: The aluminum alloy has the following components in weight ratio: Zn: 5.5-6.2wt%, Mg: 2.7-3.5wt%, Si: 3.5-4.0wt%, Cu: 1.3-2.2wt%, Fe: ≤0.5wt%, and the balance is Al.